Epidemiology and management of primary spontaneous pneumothorax: a systematic review. (20th December 2019) - Mendogni, Paolo; Vannucci, Jacopo; Ghisalberti, Marco; Anile, Marco; Aramini, Beatrice; Congedo, Maria Teresa; Nosotti, Mario; Bertolaccini, Luca; ,; D'Ambrosio, Ambra Enrica; De Vico, Andrea; Guerrera, Francesco; et al.
Abstract: : Primary spontaneous pneumothorax (PSP) is one of the most common thoracic diseases affecting adolescents and young adults. Despite the high incidence of PSP and the availability of several international guidelines for its diagnosis and treatment, a significant behavioural heterogeneity can be found among those management recommendations. A working group of the Italian Society of Thoracic Surgery summarized the best evidence available on PSP management with the methodological tool of a systematic review assessing the quality of previously published guidelines with the Appraisal of Guidelines for Research and Evaluation (AGREE) II. Concerning PSP physiopathology, the literature seems to be equally divided between those who support the hypothesis of a direct correlation between changes in atmospheric pressure and temperature and the incidence of PSP, so it is not currently possible to confirm or reject this theory with reasonable certainty. Regarding the choice between conservative treatment and chest drainage in the first episode, there is no evidence on whether one option is superior to the other. Video-assisted thoracic surgery represents the most common and preferred surgical approach. A primary surgical approach to patients with their first PSP seems to guarantee a lower recurrence rate than that of a primary approach consisting of a chest drainage positioning; conversely, the percentage of futile surgical interventions that would entail this aggressive attitude must be carefully evaluated. Surgical pleurodesis is recommended and frequently performed to limit recurrences; talc poudrage offers efficient pleurodesis, but a considerable number of surgeons are concerned about administering this inert material to young patients. Clinical trial registration number: International Prospective Register of Systematic Reviews (PROSPERO): CRD42018084247.